2017
DOI: 10.4067/s0717-95022017000200053
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations of the Foramen Transversarium in Cervical Vertebrae

Abstract: MOLINET, G. M.; ROBLES, F. P.; & ROA, I. Anatomical variations of the foramen transversarium in cervical vertebrae. Int. J. Morphol., 35(2):719-722, 2017. SUMMARY:The cervical vertebrae are recognized mainly by the presence of the foramen transversarium, which is crossed by the vertebral artery and vein, accompanied by sympathetic fibers. The main objective of this study was to observe and describe the anatomy and variations in the foramen transversarium. 121 cervical vertebrae were analyzed, including the mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
4
0
2
Order By: Relevance
“…In our study, type 1 was the most common FT shape found at C3-C6, similar to previous results from South African (Abdul et al, 2018) as shown in Table VI. However, type 4 was most common at C7, which was comparable to findings in Japanese, Chinese, Indian (Kimura et al, 1985) Chilean (Guerra et al, 2017), and South African (Abdul et al, 2018) populations. By contrast, a study in an Israeli population by Taitz et al (1978) found only type 5 FT at C7.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our study, type 1 was the most common FT shape found at C3-C6, similar to previous results from South African (Abdul et al, 2018) as shown in Table VI. However, type 4 was most common at C7, which was comparable to findings in Japanese, Chinese, Indian (Kimura et al, 1985) Chilean (Guerra et al, 2017), and South African (Abdul et al, 2018) populations. By contrast, a study in an Israeli population by Taitz et al (1978) found only type 5 FT at C7.…”
Section: Discussionsupporting
confidence: 82%
“…FT variation is clinically significant to radiologists and surgeons planning posterior operations at the lower cervical spine (C3-C7). The morphometry (such as type and diameter) and rates of variance of FT have been found to differ by population, with previous studies being conducted in Israel, Japan, China, India, Italy, Turkey, the US, Greece, Spain, Chile, South Africa, and Korea (Taitz et al 1978;Kimura et al, 1985;Sangari et al, 2015;Zibis et al, 2016;Quiles-Guiñau et al, 2017;Guerra et al, 2017;Abdul et al, 2018;Malla et al, 2018;Gupta & Agarwal, 2019). Ours was the first study to report the incidence of variance and morphometric features of the lower cervical spine FT in a Thai population.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Comparando esse dado, estudos mostraram níveis altos de confiabilidade e reprodutibilidade das medidas por essa metodologia (CAGNIE et al, 2005;KIM et al, 2012;MOLINET GUERRA;ROBLES FUENTES;ROA, 2017;SUREKA et al, 2018;ZIBIS et al, 2018ZIBIS et al, , 2016.…”
Section: Variações Anatômicasunclassified
“…melhor avaliação pré-operatória por meio da TC. Com relação à amostra, o número de indivíduos em nosso estudo não foi muito grande, mesmo sendo maior que o número de exames avaliados em estudos prévios(GUPTA et al, 2014;KAYA et al, 2011;MOLINET GUERRA;ROBLES FUENTES;ROA, 2017;TAITZ;NATHAN;ARENSBURG, 1978;ZIBIS et al, 2016). Entretanto, considerando a alta proporção de indivíduos detectados em nossa análise com variação anatômica no FT cervical, a avaliação pré-operatória dos parâmetros anatômicos do forame cervical deve ser considerada antes de realizar um procedimento cirúrgico que envolva a abordagem das vértebras cervicais.…”
unclassified